The Effectiveness of Fiscal Policy in Stimulating Economic Activity : A Review of the Literature - Mahfouz, Selma; Hemming, Richard; Kell, Michael (Washington, D.C. : International Monetary Fund, 2002)
This paper reviews the theoretical and empirical literature on the effectiveness of fiscal policy. The focus is on the size of fiscal multipliers, and on the possibility that multipliers can turn negative (i.e., that fiscal contractions can be expansionary). The paper concludes that fiscal multipliers are overwhelmingly positive but small. However, there is some evidence of negative fiscal multipliers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet